The current issues of limitations of human rights during the COVID-2019 pandemic - Seifullina, A.B.; Smatlayev, B.M.; Nazarkulova, L.T. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The question of limiting human rights is inherently complex and controversial. Restrictions on human rights are introduced to protect the rights themselves, but they may lead to their violations as well. Restrictions on human rights must be proportionate, balanced, necessary, temporary, and expedient. The issue of restrictions on human rights during COVID 2019 is of great interest. The government should first seek to minimize the negative consequences that may arise from their implementation before introducing restrictions. Governments should seek to balance restricting and respecting human rights and freedoms. Restrictions take place in all areas of our lives, as we all know. Restrictive measures must be implemented by observing the principles of transparency, openness, and justification, and the inadmissibility of abuse of power by government agencies. The article attempts to identify the specifics of restrictive measures during the COVID-2019 pandemic taken in various states and the Republic of Kazakhstan. A review of the scientific works was made to determine the main features and criteria of restrictions on human rights. The restriction of human rights in Kazakhstan should be made within the current legislative framework, whilst also taking into account the positive practices observed in developed nations. This approach should also be applied in emergencies.